Cutaneous, gastrointestinal, hepatic, endocrine, and renal side-effects of anti-PD-1 therapy. (June 2016) - Hofmann, Lars; Forschner, Andrea; Loquai, Carmen; Goldinger, Simone M.; Zimmer, Lisa; Ugurel, Selma; Schmidgen, Maria I.; Gutzmer, Ralf; Utikal, Jochen S.; Göppner, Daniela; Hassel, Jessica C.; Meier, Friedegund; et al.
Abstract: Background: Anti-programmed cell death receptor-1 (PD-1) antibodies represent an effective treatment option for metastatic melanoma as well as for other cancer entities. They act via blockade of the PD-1 receptor, an inhibitor of the T-cell effector mechanisms that limit immune responses against tumours. As reported for ipilimumab, the anti-PD-1 antibodies pembrolizumab and nivolumab can induce immune-related adverse events (irAEs). These side-effects affect skin, gastrointestinal tract, liver, endocrine system and other organ systems. Since life-threatening and fatal irAEs have been reported, adequate diagnosis and management are essential. Methods and findings: In total, 496 patients with metastatic melanoma from 15 skin cancer centers were treated with pembrolizumab or nivolumab; 242 side-effects were described in 138 patients. In 116 of the 138 patients, side-effects affected the skin, gastrointestinal tract, liver, endocrine, and renal system. Rare side-effects included diabetes mellitus, lichen planus, and pancreas insufficiency due to pancreatitis. Conclusion: Anti-PD1 antibodies can induce a plethora of irAEs. The knowledge of them will allow prompt diagnosis and improve the management resulting in decreased morbidity. Highlights: Anti-PD-1 antibodies can induce a plethora of immune-related adverse events (irAEs). IrAEs of the skin, gastrointestinal tract, liver, endocrine and renal system were analyzed. Diabetes mellitus, lichen planus and pancreas insufficiency due to pancreatitis were reported. If symptoms are autoimmune-related, prompt treatment has to be initiated to reduce morbidity. Since irAEs can start asymptomatic or with minimal symptoms, careful monitoring is essential.